MONOCLONAL GAMMOPATHY - Anwar, Mohammad Shamim (Journal of Ayub Medical College Abbottabad, 1996)
A 63 years old male patient with known ischaemic heart disease presented with incontinence and weakness in the legs which was progressively increasing over the past 4 months and recently he noticed mild weakness in the upper limbs as well. Neurological examination revealed a fully conscious and intelligent gentleman with normal speech, a supple neck and intact cranial nerves. Lower limb examination revealed mild wasting, no fasciculation, a grade 3 power, absent knee jerks, and plantars could not be elicited. The position and vibration senses were absent and sense of pain and temperature were impaired, the perineal sensations were intact and the anal reflex was present. The upper limb examination revealed 4 weakness with sluggish tendon jerks. The CSF examination showed a total protein of 120 mg/100ml with normal cell count. His plasma protein electrophoresis showed monoclonal gammopathy. The urine did not show any light chains and the bone marrow examination was normal. His nerve conduction studies and electromyography confirmed a polyneuropathy. The patient received five sessions of plasmapheresis after which there was some increase in power in both the upper and lower limbs. The patient was then started on immunoglobulin at the rate of 400 mg/kg/day which came out to 25 gm per day. After five courses of Gamma Immune-N his lower limb power increased to 4 and he was able to walk with support.